Periodic mesoporous silicas and organosilicas: an overview towards catalysis - Shylesh, S.; Samuel, Prinson P.; Sisodiya, Sheetal; Singh, A. P. (Catalysis Surveys from Asia, 2008)
Micelle-templated mesoporous and organic-inorganic hybrid mesoporous materials are important in many fields of material research, especially for hosting catalysts in confined space. Among this class, the recent discovery of periodic mesoporous organosilicas (PMOs) represent an exciting new group of organic-inorganic nanocomposites targeted for a broad range of applications ranging from catalysis to microelectronics. Compared to the earlier generation of organic-inorganic hybrid mesoporous samples, obtained by the cocondensation reaction or by the grafting reaction, PMOs represent the right combination of organic and inorganic groups in the frame wall positions. This article reviews the current state of art in organic-inorganic hybrid mesoporous material research with special emphasis over periodic mesoporous organosilica materials having various redox centers (Ti, V, Cr) suitable for oxidation reactions as well as acidic sites (Al, -SO(3)H) for the organic transformation of bulky molecules.
Keywords: Acid catalysis; epoxidation; Mesoporous organosilicas; Organic-inorganic hybrid materials

Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine